2013
DOI: 10.1021/ie401387s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Green Corrosion Inhibition by Alkaloid Extracts of Ochrosia oppositifolia and Isoreserpiline against Mild Steel in 1 M HCl Medium

Abstract: Alkaloid extracts of leaves (OOL) and bark (OOB) of Ochrosia oppositifolia, as well as isoreserpiline (ISR), the major alkaloid isolated from OOL and OOB, were investigated as potential corrosion inhibitors for mild steel (MS) in 1 M HCl medium. The inhibition properties of these phytoconstituents were studied using electrochemical techniques (potentiodynamic polarization measurements and electrochemical impedance spectroscopy, EIS) and scanning electron microscopy (SEM). The results indicated that these green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…13c shows the change of R ct + R f values with incubation time. R ct + R f values are closely related to the corrosion rates, a lower value for a higher corrosion rate [35]. As seen in Fig.…”
Section: Eis Analysismentioning
confidence: 66%
“…13c shows the change of R ct + R f values with incubation time. R ct + R f values are closely related to the corrosion rates, a lower value for a higher corrosion rate [35]. As seen in Fig.…”
Section: Eis Analysismentioning
confidence: 66%
“…This shows that there is agreement between the amounts of charge that can be stored (i.e. capacitance) and the discharge velocity in the interface (t) [22]. The double-layer between the charged metal surface and the electrolyte solution is considered as an electrical capacitor.…”
Section: Eis Measurementmentioning
confidence: 60%
“…From AFM analysis it was observed that Caulerpin forms surface protective film at the metal-electrolyte interfaces. Raja et al [96] studied the inhibition effect of alkaloids leaves and bark extracts of Ochrosia oppositifolia as well as one pure indole containing alkaloid namely isoreserpiline (ISR), on mild steel corrosion in 1 M HCl. The inhibition effect of extracts and ISR was evaluated using SEM, EIS, PDP, FT-IR and DFT methods.…”
Section: Indole Based Alkaloids As Corrosion Inhibitorsmentioning
confidence: 99%